2022
DOI: 10.3390/ijms23031208
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Role of Vitamin C in Neurodevelopment

Abstract: The maternal diet during pregnancy is a key determinant of offspring health. Early studies have linked poor maternal nutrition during gestation with a propensity for the development of chronic conditions in offspring. These conditions include cardiovascular disease, type 2 diabetes and even compromised mental health. While multiple factors may contribute to these outcomes, disturbed epigenetic programming during early development is one potential biological mechanism. The epigenome is programmed primarily in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 218 publications
0
7
0
Order By: Relevance
“…Vitamin C (vitC) plays a key neuroprotection role in the postnatal brain against glutamateinduced neurodegeneration, and functions as a cofactor of epigenetic enzymes such as ten-eleven translocation methylcytosine dioxygenases (TETs) and the Jumonji C domain-containing histone lysine demethylases to facilitate epigenetic modification of the postnatal brain. 57,[77][78][79] The brain undergoes extensive epigenetic modification during postnatal development. 77 The brain epigenome modification at the postnatal period is required for hypocampal neurogenesis in adult life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C (vitC) plays a key neuroprotection role in the postnatal brain against glutamateinduced neurodegeneration, and functions as a cofactor of epigenetic enzymes such as ten-eleven translocation methylcytosine dioxygenases (TETs) and the Jumonji C domain-containing histone lysine demethylases to facilitate epigenetic modification of the postnatal brain. 57,[77][78][79] The brain undergoes extensive epigenetic modification during postnatal development. 77 The brain epigenome modification at the postnatal period is required for hypocampal neurogenesis in adult life.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that a lack of REST in the placenta induced an adaptive metabolic response of the offspring brain during development from the postnatal to adult life. Important brain metabolites such as vitamin C (ascorbate), lactate, creatine, and glutamate [54][55][56][57][58] were associated with this metabolic response (Table 2). Lactate fuels brain energy, 54 glutamate and creatine help the brain respond to stress conditions, including cerebral hypoxic conditions, 55,56 and ascorbate acts as a co-factor of specific epigenetic enzymes in the brain.…”
Section: Ablation Of Placental Rest Impacted Metabolism Of the Offspr...mentioning
confidence: 99%
“…This could be due to a number of factors, such as vomiting, non-compliance, or low bioavailability of the supplement. Vitamin C has important roles to play in epigenetic regulation during development [ 40 ] and is also a cofactor for collagen synthesis, with supplementation showing positive benefits regarding attenuating premature rupture of membranes (RR 0.66, 95% CI 0.48–0.91) [ 41 ]. Low vitamin C status has also been associated with higher odds of developing pre-eclampsia (OR 3.8, 95% CI 1.7–8.8) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…They assessed the methylation status of H3 histone by western blots and reported that ascorbic acid reversibly reduced the level of H3K36me2/3. [ 104 ] Extended studies showed that ascorbic acid‐mediated H3K36 demethylation was accomplished by JHDM1A/1B [ 104–107 ] X‐ray crystallography revealed that the catalytic site of JHDM family members resides at the N‐terminal JmjN domain. In this domain, a long helix and two short helices were sandwiched between two β‐strands.…”
Section: Epigenetic Modulation Of Dna By Ascorbic Acidmentioning
confidence: 99%